Kutkot - Valdecantos, Renato Elijah M. (Animo Repository, 2022)
Kutkot is a 20 minute short film that falls under the horror genre. The driving concept of the short film is grief from the loss of a loved one; and the mental and emotional suffering it brings. Andres yearns for his dead mother's presence. He learns of an ancient ritual called “Kutkot '' from his house helper, as she shares this to him because she sees the depths of his despair. Andress attempts to perform the said ritual in hopes to bring his mother back to life. He performs each step of the ritual, but falters in some parts given the limited amount of time and resources. After the ritual, it seemed like nothing happened. But soon, supernatural events begin to occur in their household. Eventually, the mother makes her presence felt. But something is not completely right. In the dawn of her return, the house helper is found dead inside a black trash bag-strangled by some unknown assailant and a look of terror in her eyes. A few days after the inquest, the son sees his mother in the kitchen. This fills him with joy and some unease. In the few hours, he notices that the mother is acting strange. He decides to tell his estranged father about what he and their helper has done, and on the latter part they face the consequences of disrupting the natural way of life. 1080p MP4 format.